Smallholder Dairy Farmers’ Group Development in Bhutan: Strengthening Rural Communities through Group Mobilization - Sonam, Thubten; Martwanna, Niwat (JPAIR Multidisciplinary Research, 2012)
This paper describes the mobilization processes of Smallholder Dairy Farmers’ Groups (SDFG) and its relevance to the process of community development in an integrated crop livestock forestry farming system in Bhutan. The group approach aims to ensure effective delivery of dairy services for strengthening collective self-help capacity, promoting self-reliance, group cooperation and solidarity of poor rural farmers through collective action. Data for the study were generated through focused group interviews and workshop organized among the relevant stakeholders involved in formation and development of dairy farmers’ groups. The study found that the group mobilization processes demanded new competences in managing the different stages of group formation and development processes with professional support backed by new knowledge and skills. While the government encourages and supports the mobilization of dairy groups, the process of forming a group is still difficult due to a wide range of technical, socio-cultural, organizational, and physical challenges. However, despite the challenges and difficulties, SDFGs are slowly contributing to the enhancement of smallholder dairy farmers’ skills, achievement of economies-of-scale and improving their bargaining power. The SDFGs are helping to build trust among members, instill positive changes in attitude and commitment to achieve group’s success motivated by accrued financial benefits and easy access to other services. The formation and development of dairy groups needs to be supported by well-trained competent group mobilizers who are able to manage and facilitate group processes effectively.